Comparison of Microneedling with Platelet-Rich Plasma versus Distilled Water for Atrophic Acne Scar - Ghaus, Iqra; Mashhood, Asher Ahmad; Yousaf, Farrah; Rathore, Hassan Sajjad; Yasmin, Ghazala; Khan, Shumaila (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the effectiveness of microneedling with platelet-rich plasma (PRP) and distilled water for the treatment of atrophic acne scars.Study Design: Quasi-experimental study.Place and Duration of Study: Department of Dermatology, Pakistan Air Force Hospital, Rafiqui, Shorkot Cantt Pakistan, from Jan to Jun 2023.Methodology: The study included 80 patients, aged 15 to 40 years, of both genders with atrophic acne scars. An equal patients were divided into 2 groups. In Group-A, 2 mL of PRP was applied simultaneously over the face, along with micro-needling. In Group-B, distilled water was used instead of PRP. A total of 3 sessions of micro-needling were performed at monthly intervals in both groups. Each patient was followed up for 3 months after the final session. Effectiveness was noted after 6 months of the 1st treatment session.Results: The mean age of 26.825±3.32 years in Group-A and the mean age of 26.80±3.26 years in Group-B. Effectiveness was observed in 20(50.0%) patients in Group-A as compared to 5(12.5%) patients in Group-B (p-value